A Landscape . . . with Figures:: Tourism and Environment on Prince Edward Island - MacDonald, Edward (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2011)
Abstract Its pastoral landscape has long permeated Prince Edward Island’s tourist appeal and shaped its cultural identity. Nineteenth-century tourist promotion extolled the health benefits of sea breezes for travellers fleeing the summer swelter of urban America but, by the interwar period, tourism literature had begun to equate the Island’s arcadian countryside with a pre-industrial, rural order. Post-war tourism marketing continued to eulogize the Island as an antidote to North Americans’ urban-industrial angst, but in the new millennium both the commodified pastoral landscape and rural identity faced a new challenge as economic pressures drove most farmers out of business.